2020
DOI: 10.3390/ijerph17041389
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Clinostomum complanatum (Trematoda: Digenea) in European Perch (Perca fluviatilis) from an Italian Subalpine Lake: A Risk for Public Health?

Abstract: Clinostomum complanatum, a digenean trematode of the Clinostomidae family, is a fish-borne zoonotic parasite responsible for Halzoun syndrome in humans and is transmitted through the consumption of raw or undercooked freshwater fish. Of the total of 112 specimens of European perch (Perca fluviatilis) sampled from a subalpine lake (Lake Endine) in North Italy in 2019, 21 (18.75%) tested positive for encysted metacercariae in the fillet. This study reports the first isolation of C. complanatum in P. fluviatilis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…The eggs remain viable and infective for up to 2 years, and the larvae can survive in the intermediate host for more than 1 year [25]. Piscivorous birds, being a definitive host for numerous parasite species, contribute to their spread [16,37]. The cormorant population has increased in number and area in recent decades in northern Italy [38], where it is concentrated around large lakes and other pre-alpine water basins [38].…”
Section: Discussionmentioning
confidence: 99%
“…The eggs remain viable and infective for up to 2 years, and the larvae can survive in the intermediate host for more than 1 year [25]. Piscivorous birds, being a definitive host for numerous parasite species, contribute to their spread [16,37]. The cormorant population has increased in number and area in recent decades in northern Italy [38], where it is concentrated around large lakes and other pre-alpine water basins [38].…”
Section: Discussionmentioning
confidence: 99%
“…The spatial distribution of D. latus can also give us information about its life cycle. Ineffective sewage treatment systems are known to permit the contamination of lakes with D. latus eggs released by infected humans [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In fact, fecal pollution plays a key role in maintaining the parasite’s life cycle and the persistence of diphyllobothriasis in the subalpine area [ 3 , 4 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the European perch ( Perca fluviatilis ) is the most common host for D. latus , the Northern pike ( Esox lucius ) acts as a paratenic host, and the burbot ( Lota lota ) plays a minor role in human diphyllobothriasis [ 4 ]. P. fluviatilis has a wide distribution throughout the Northern Hemisphere and it is a suitable host for several endohelminth and zoonotic parasites [ 4 , 5 , 6 , 7 , 8 ]. The European perch is a commercially important fish, especially for local fisheries; it is often used in raw and cooked traditional dishes prepared at home and in restaurants [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in this study, we first combine morphological and molecular techniques to identify clinostomatids infecting cultured and wild tilapia species in Aswan Governorate, Egypt. The development of effective strategies and proactive measures for these parasitic diseases is aided by definitive diagnosis.Clinostomatids infect a wide variety of fish species around the world including about 13 families and 77 fish species indicating low host specificity, but interestingly, in Egypt only cichlids are infected with these parasites(El-Naffar et al, 1983;El-Shahawy et al, 2017;Ezzat et al, 2012;Hamouda & Abd Alkareem, 2021;Hefnawy et al, 2019; Li et al, 2018;Mahmoud et al, 2014;Menconi et al, 2020;Montes et al, 2020;Saoud & Wannas, 1984;Simsek et al, 2018;Taher, 2009), as confirmed by this study.In Egypt, several authors reported yellow grub disease in tilapia species caused by C. phalacrocoracis, C. complanatum, C. tilapiae and Clinostomum spp. metacercariae infections, but no one reported C. cutaneum.…”
mentioning
confidence: 99%